2021
DOI: 10.1002/anie.202016064
|View full text |Cite
|
Sign up to set email alerts
|

TM LDH Meets Birnessite: A 2D‐2D Hybrid Catalyst with Long‐Term Stability for Water Oxidation at Industrial Operating Conditions

Abstract: Efficient noble‐metal free electrocatalyst for oxygen evolution reaction (OER) is critical for large‐scale hydrogen production via water splitting. Inspired by Nature's oxygen evolution cluster in photosystem II and the highly efficient artificial OER catalyst of NiFe layered double hydroxide (LDH), we designed an electrostatic 2D‐2D assembly route and successfully synthesized a 2D LDH(+)‐Birnessite(−) hybrid. The as‐constructed LDH(+)‐Birnessite(−) hybrid catalyst showed advanced catalytic activity and excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…[ 6b,10 ] Similar results were also observed for metal‐organic frameworks. [ 6b,9a ] These findings inspire us to upgrade the design of NiFe LDH through a biomimetic process to accelerate the sluggish kinetics. [ 11 ] Nevertheless, understanding the dynamic behaviors of layered double hydroxide with biomimetic ligand for alkaline OER remains highly challenging.…”
Section: Introductionsupporting
confidence: 67%
“…[ 6b,10 ] Similar results were also observed for metal‐organic frameworks. [ 6b,9a ] These findings inspire us to upgrade the design of NiFe LDH through a biomimetic process to accelerate the sluggish kinetics. [ 11 ] Nevertheless, understanding the dynamic behaviors of layered double hydroxide with biomimetic ligand for alkaline OER remains highly challenging.…”
Section: Introductionsupporting
confidence: 67%
“…[34] Interesting, the binding energy of both Co 2p and Ni 2p in the NiFeCoP/NF has an around 0.5 eV positive shift compared with those in the NiFe LDH@ZIF-67/NF, revealing the formation of more Ni and Co species in high-valence states resulting from the interface charge redistribution and the construction of heterogeneous interfaces, these shifts are beneficial to reduce the energy barrier. [24,35,36] For the XPS spectrum of Fe 2p (Figure 2c), the weak peaks located at 720.0 (Fe 2p 1/2 ) and 706.0 eV (Fe 2p 3/2 ) would be assigned to the Fe in Fe 2 P. [37] The peaks observed at 722.5 and 710.4 eV would be attributed to Fe 2 + 2p 1/2 and Fe 2 + 2p 3/2 , respectively, while the two peaks with the binding energy of 725.0 and 713.0 eV could be ascribed to Fe 3 + 2p 1/2 and Fe 3 + 2p 3/2 , respectively, and the signals at 731.0 and 716.5 eV can be assigned to the satellite peaks. [38] Moreover, the XPS spectrum of P 2p in NiFeCoP/NF is displayed in Figure 2d.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Chen et al found that the use of doping can enhance the OER activity of NiFe‐LDH, improve the diffusion of proton receptors, and greatly improve the stability 40 . Moreover, the latest research found that the design and synthesis of the electrostatic 2D‐2D assembly route increased the flexible interlayer of NiFe‐LDH and enabled the Fe‐3d orbital move upward for efficient industrial applications 41 . Besides, other kinds of double metal hydroxides also exhibited excellent tunable OER performance 42‐44 .…”
Section: Introductionmentioning
confidence: 99%